2014
DOI: 10.1227/neu.0000000000000451
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Single Twist-Drill Access Device for Multimodal Intracranial Monitoring

Abstract: Hummingbird Synergy is a novel single-port access device for multimodal intracranial monitoring that can be placed safely at the bedside or in the operating room with placement accuracy and has a complication profile similar to or better than that for standard external ventricular drains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 41 publications
0
7
0
1
Order By: Relevance
“…One study concluded that the Hummingbird Synergy Ventricular System could be safely implanted at the bedside or in the operating room with 91% success and that the complications that arose from the implantation were similar if not less than those of other EVDs and intraparenchymal devices. 11…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study concluded that the Hummingbird Synergy Ventricular System could be safely implanted at the bedside or in the operating room with 91% success and that the complications that arose from the implantation were similar if not less than those of other EVDs and intraparenchymal devices. 11…”
Section: Resultsmentioning
confidence: 99%
“…One study concluded that the Hummingbird Synergy Ventricular System could be safely implanted at the bedside or in the operating room with 91% success and that the complications that arose from the implantation were similar if not less than those of other EVDs and intraparenchymal devices. 11 Intraparenchymal pressure monitoring. Intraparenchymal monitors involve the placement of a fiberoptic, strain gauge, or air bladder device within the brain parenchyma.…”
Section: Intracranial Pressurementioning
confidence: 99%
“…Chohan et al (2014) published their institution’s five year experience with use of the Hummingbird ® Synergy Ventricular System. In that study, of 275 devices, 251 (91%) were successfully placed on the first attempt, 4 (2%) on the second attempt, and 18 (7%) on >2 attempts.…”
Section: Introductionmentioning
confidence: 99%
“…In that study, of 275 devices, 251 (91%) were successfully placed on the first attempt, 4 (2%) on the second attempt, and 18 (7%) on >2 attempts. In the literature, the rate of misplaced catheters ranges from 6% to 45% (Chohan et al 2014). The authors concluded that the system can be placed safely and effectively at the bedside or in the operating room and that it carries a similar or favorable complication profile when compared to other ventricular ICP monitoring systems (Chohan et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Έχει γίνει επίσης αναφορά σε μια οξεία μορφή αποφολιδωτικού γλαυκώματος που μιμείται γλαύκωμα κλειστής γωνίας, με πίεση ίσως άνω των 50, κόκκινο μάτι και συχνά οίδημα κερατοειδούς (Gillies and West 1977;Gillies and Brooks 1988). (Bocca C et al 2014;Chohan MO 2014). Αυτό είναι πολύ ενδιαφέρον, καθώς και στο ψευδοαποφολιδωτικό σύνδρομο υπάρχουν ενδείξεις ότι συμβαίνει επιθήλιο-μεσεγχυματική μετατροπή (Laczko R. et al 2014).…”
Section: εξωφθάλμιες εντοπίσεις ψευδοαποφολιδωτικού υλικούunclassified